Efficient oxidation of ethyl benzene using in situ generated molybdenum acetylide oxo-peroxo complex as recyclable catalyst - Khomane, Sonali B.; Doke, Dhananjay S.; Dongare, M. K.; Halligudi, S. B.; Umbarkar, S. B. (Applied Catalysis A-General, 2017)
Selective oxidation of various alkanes/alkyl aromatics to corresponding carbonyl compounds has been carried out with very high conversion (similar to 98%) and selectivity (up to 100%) for carbonyl compounds using cyclopentadienyl molybdenum acetylide complex, CpMo(CO)(3)(C CPh) (1) as catalyst and tert-butyl hydrogen peroxide (TBHP) as an oxidant and turnover number (TON) of 88 was obtained with turnover frequency (TOF) of 2.45 h(-1). Mo acetylide oxo-peroxo species is formed in situ by reaction of 1 with TBHP during the course of reaction as catalytically active species. Interestingly even though the catalytically active species is homogeneous in nature it could be recycled very easily by recovering the catalytically active species as solid after addition of diethyl ether, and separating the products into organic phase. In the case of ethyl benzene oxidation, even after three recycles no appreciable loss in ethyl benzene conversion and acetophenone selectivity was observed. This complex showed high catalytic activity for the oxo functionalization of other alkyl aromatics and alkanes such as substituted ethyl benzenes, toluene as well as cyclohexane. TBHP was found to be more efficient oxidant than hydrogen peroxide for this oxidation. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Alkyl aromatics; Carbonyl compounds; Homogeneous catalysis; Molybdenum acetylide complex; Oxo-peroxo species

Bimetallic Au-Ag/Al2O3 as efficient catalysts for the hydrocarbon selective reduction of NOx from lean burn engine exhaust - More, P. M.; Dongare, M. K.; Umbarkar, S. B.; Granger, P.; Dujardin, C. (Catalysis Today, 2018)
Catalytic properties of Au-Ag/Al2O3 catalysts, prepared by successive impregnation, have been investigated for the hydrocarbon selective catalytic reduction (HC-SCR) of NOx. The performances of pre-reduced and aged catalysts were evaluated on synthetic reaction mixtures with gas compositions representative of the exhaust of Diesel powered engines. An optimal 2 wt.% Ag loading was chosen and the order of introduction during sequential impregnation of Ag or Au on respectively pre-impregnated Au/Al2O3 and Ag/Al2O3 substrates was investigated revealing drastic changes on the catalytic properties after aging. XPS analysis shows a significant silver enrichment irrespective of the preparation route and aging conditions whereas ex situ UV-vis DRS analysis reveals significant electronic disturbances which reflect different interactions between Au and Ag in fresh and aged Au-Ag/Al2O3 and Ag-Au/Al2O3 catalysts. As a consequence, significant rate enhancements in NOx conversion were observed with the superior performance of Au-Ag/Al2O3 but a lower resistance to deactivation at high temperature explained by different behaviour towards redispersion/agglomeration processes highlighted from TEM observations. (C) 2016 Elsevier B.V. All rights reserved.

Hydrophobic WO3/SiO2 catalyst for the nitration of aromatics in liquid phase - Kulal, A. B.; Kasabe, M. M.; Jadhav, P. V.; Dongare, M. K.; Umbarkar, S. B. (Applied Catalysis A-General, 2019)
WO3/SiO2 solid acid catalyst synthesized using sol gel method has shown promising activity (up to 65% conversion) for aromatic nitration in liquid phase using commercial nitric acid (70%) as nitrating agent without using any sulfuric acid. The water formed during the reaction as well as water from dilute nitric acid (70%) was removed azeotropically, however due to the hydrophilic nature of the catalyst, some water gets strongly adsorbed on catalyst surface forming a barrier layer between catalyst and organics. This prevents effective adsorption of substrate on catalyst surface for its subsequent reaction. To improve the activity further, the hydrophilic/hydrophobic nature of the catalyst was altered by post modification by grafting with commercial short chain organosilane (Dynasylan 9896). The modified 20% WO3/SiO2 catalyst when used for o-xylene nitration in liquid phase, showed significant increase in the conversion from 65% to 80% under identical reaction conditions. Catalyst characterization revealed decrease in the surface area of 20% WO3/SiO2 from 356 m(2)/g to 302 m(2)/g after grafting with Dynasylan 9896. The fine dispersion of WO3 particles (2-5 run) on silica support was not affected due to modification. NMR and FTIR study revealed the decrease in surface hydroxyl groups imparting hydrophobicity to the catalyst. Interestingly the total acidic sites of the catalyst remained almost unaltered (0.54 mmol NH3/g) even after modification. Even though, the acidity and other characteristics of the catalyst did not change appreciably, there was a considerable increase in the o-xylene conversion which can be ascribed to the hydrophobic nature of the catalyst.
Keywords: Aromatic nitration; grafting; heterogeneous catalysis; Hydrophobic; Sol-gel synthesis